2022
DOI: 10.1038/s41419-022-05139-3
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis induces RIPK1-dependent death of glioblastoma stem cells via acid-sensing ion channel 1a

Abstract: Eliciting regulated cell death, like necroptosis, is a potential cancer treatment. However, pathways eliciting necroptosis are poorly understood. It has been reported that prolonged activation of acid-sensing ion channel 1a (ASIC1a) induces necroptosis in mouse neurons. Glioblastoma stem cells (GSCs) also express functional ASIC1a, but whether prolonged activation of ASIC1a induces necroptosis in GSCs is unknown. Here we used a tumorsphere formation assay to show that slight acidosis (pH 6.6) induces necrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 64 publications
3
22
0
Order By: Relevance
“…5c). These ndings are similar to the effect of acidic pH on GSCs [24]. In contrast, maintenance of mouse neurons in acidic medium for 24 hours induces ASIC-mediated cell death [25,[46][47][48][49].…”
Section: Extracellular Acidi Cation Reduces Cell Viability But Does N...supporting
confidence: 61%
See 1 more Smart Citation
“…5c). These ndings are similar to the effect of acidic pH on GSCs [24]. In contrast, maintenance of mouse neurons in acidic medium for 24 hours induces ASIC-mediated cell death [25,[46][47][48][49].…”
Section: Extracellular Acidi Cation Reduces Cell Viability But Does N...supporting
confidence: 61%
“…Functional homomeric ASIC1a is also expressed in glioblastoma stem cell lines (GSCs) [22]. While ASICs do not contribute to the aggressive migration of GSCs in vitro [23], activation of ASIC1a reduces tumor sphere formation of GSCs by inducing a Nec1-dependent cell death that is related to but not identical with necroptosis [24]. Nec-1 is an inhibitor of receptor interacting protein kinase 1 (RIPK1) and it had previously been demonstrated that ASIC1a activation induces a RIPK1-dependent cell death mechanism in neurons, which could contribute to the neurodegeneration accompanying ischemic stroke [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sizes of spheres grown at pH 6.6 were smaller than those of spheres grown at pH 7.4 (Fig. 5b-c), which was expected, as the doubling time in pH 6.6 is longer for R54 GSCs [5]. It is unlikely, however, that the smaller sphere sizes affected the interpretation of this experiment, because, if anything, fewer cells should grow out of smaller spheres.…”
Section: Pi3k But Not K Ca 31 Modulates Ph-dependent Migrationmentioning
confidence: 51%
“…3d). Finally, we assessed the outgrowth of spheres using two independent R54 lines with an ASIC1a knockout [5]. Also ASIC1a knockout did not affect migration (Fig.…”
Section: Asic1 Asic2 and Asic3 Do Not Modulate Ph-dependent Migrationmentioning
confidence: 99%
See 1 more Smart Citation